Causal association between common rheumatic diseases and glaucoma: a Mendelian randomization study - Meng, Yang; Tan, Zongbiao; Su, Yu; Li, Lu; Chen, Changzheng (Frontiers in Immunology, 2023)
Background: Autoimmunity and inflammation are the main characteristics of rheumatic diseases and have both been found to be related to glaucoma. However, it remains unclear whether rheumatic diseases increase the risk of glaucoma. Here, we performed an Mendelian randomization (MR) analysis to investigate the causal effects of six common rheumatic diseases on glaucoma.Methods: Six rheumatic diseases were included: ankylosing spondylitis (AS), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sicca syndrome/Sjögren's sydrome (SS), dermatomyositis (DM), and gout. Glaucoma included primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG). Genetic variants associated with these rheumatic diseases and glaucoma were extracted from the genome-wide association studies and FinnGen8 database, respectively. First, aA two-sample MR was used to investigate the potential causal association. Then a multivariable MR was conducted to further verify the results. Inverse variance weighted MR analysis was used as the main method, together with several sensitivity analyses.Results: Two-sample MR suggests AS is related to a higher risk of both POAG [odds ratio (OR) = 1.